Utilization of food waste for bioacids, bioplastics and biofuel production - Abdul Rahman, Nor'aini; Hafid, Halimatun Saadiah; Omar, Farah Nadia; Mohd Yasin, Nazlina Haiza; Hassan, Mohd Ali (2014)
Food waste is the major component in municipal solid waste (MSW) accounted 20-54% of the total waste. It is high in organic matter, volatile solids and moisture content. Thus, it becomes the main source of odor, decay, vermin attraction, groundwater contamination and greenhouse gas emission. Currently, landfill is the sites for disposal of MSW in Malaysia. Rapid urbanization and population increment become more challenging as the number of MSW generated rises and led to shortage of landfill site. Therefore the strategy to convert food waste to value added products would be a solution to reduce volume of MSW, minimize environmental problems and generate profit. Based on the characteristic of food waste with high total solid, COD and carbohydrate content, it has potential to be converted to value-added products such as organic acids, fermentable sugar, bioplastic, bioethanol and biohydrogen. We have successfully produced and enhanced the value-added products from food waste in flask and bioreactor through process optimization. For the production of biohydrogen, anaerobic fermentation of food waste was conducted in a bioreactor at thermophilic temperature. The highest biohydrogen production was 79 mmol H2L-1d-1. Food waste was enzymatically converted to fermentable sugar before it was used as fermentation feedstock for bioethanol production by local isolated yeast. The experiment was carried out in flask with the highest ethanol productivity was 0.5 gL-1h-1 with 98% conversion efficiency. Optimization of anaerobic digestion of food waste to organic acids was also conducted in shake flask using statistical analysis. The organic acid produced was successfully used as carbon substrate for polyhydroxybutyrate (bioplastic) production by Cupriavidus necator. The highest polyhydroxybutyrate productivity (0.242gL-1h-1) was achieved in fed-batch culture. Food waste shows a suitable biomass and renewal source to be exploited especially for biofuel production in order to reduce dependence on fossil fuel. More effort should be focused to upscale the conversion of food waste for biofuel production and establish biorefinery plant.